Graphene‐Encapsulated Copper tin Sulfide Submicron Spheres as High‐Capacity Binder‐Free Anode for Lithium‐Ion Batteries. Issue 5 (28th February 2017) - Fu, Lin; Wang, Xiaogang; Ma, Jun; Zhang, Chuanjian; He, Jianjiang; Xu, Hongxia; Chai, Jingchao; Li, Shizhen; Chai, Fenglian; Cui, Guanglei
Abstract: Sn‐based sulfides are potential anode materials for lithium‐ion batteries (LIBs); nevertheless, they typically suffer from poor cycle stability resulted from the huge volume variation during lithium‐ion insertion and extraction. Herein, we successfully fabricated the multiphase Cu2 Sn3 S7 /Cu2 SnS3 /SnS2 (CTS) submicron spheres uniformly incorporated with reduced graphene oxide nanosheets (CTS@RGO). This binder‐free hybrid CTS@RGO paper exhibits favorable capacity retention as an anode of LIBs (965 mAh g −1 after 300 cycles at current density of 500 mA g −1 ), as well as better rate capability and high initial coulombic efficiency compared with that of a pristine CTS anode. The enhanced electrochemical performance can be ascribed to the introduction of graphene as a buffer to accommodate large volume changes and to maintain structural integrity of electrode. Abstract : On best behavior : A self‐standing and binder‐free composite of Cu2 Sn3 S7 /Cu2 SnS3 /SnS2 (CTS) submicron spheres incorporated with reduced graphene oxdie (RGO) nanosheets (CTS@RGO) is successfully prepared as an anode material for lithium‐ion batteries. The lithium storage behavior of the CTS@RGO composite as an anode material is subsequently investigated.